Complexity analysis of the VVenC versus VVC encoder - Touzani, Hajar; Errahimi, Fatima; Mansouri, Anass; Ahaitouf, Ali (Institute of Advanced Engineering and Science, 2024)
The joint video experts team (JVET) has recently finalized a next-generation open-source video codec, called versatile video coding (VVC). The new standard presents a higher gain in the run time and rate compressions. Based on the reference software (VTM, VVC Test Model) of VVC, an optimized encoder was developed these last years resulting in a fast and efficient encoder, called Fraunhofer versatile video encoder (VVenC). Based on the Bjontegaard methodology and the GPROF profiling tool, this paper presents a technical complexity analysis and comparison of both VVC and VVenC. The appropriate comparisons cover the percentage taken by each block in terms of processing time and the resulting whole encoding time. The peak signal-to-noise ratio (PSNR) and bit rate between VVC and VVenC encoders based on the common test conditions manual are also analyzed and compared. The profiling results show that the VVenC encoder presents a maximum gain of runtime and bit rate of 90% and 20% respectively in classes A and D test sequences, compared to the VVC encoder.